THEORETICAL APPROACHES TO SCIENTIFIC ANALYSIS OF IMPAIRMENTS IN SOCIAL-ECONOMIC DEVELOPMENT OF REGIONS (Marketing Journal, 2025)
This article provides a scientific analysis of the disparities in the socio -economic development of regions and highlights the main theoretical approaches used in the study of this process. The causes of disparities in regional development, their 279 consequences, and effective strategies for eliminating this situation are considered. Also, various theories are analyzed from the perspective of economic geography, institutional economics, and regional policy, and their possibilities for practical applic ation are assessed. The article provides detailed information on modern approaches to reducing regional inequality, the role of state and territorial governance, and the importance of systemic reforms. The results of the study include scientific and practi cal recommendations aimed at ensuring the sustainable development of regions and reducing existing disparities.
Keywords: regional development; socio -economic disparities; theoretical approaches; economic geography; regional policy; institutional economics; inequality; sustainable development; public administration; territorial reforms